Far-Detuning Laser Frequency Disturbance Suppression for Atomic Sensor Based on Intrinsic Fiber Fabry–Pérot Cavity - Guanghui Li; Lihong Duan; Xinxiu Zhou; Wei Quan (Photonics)
The method of laser far-detuned frequency locking is proposed based on a fiber Fabry–Perot cavity which transfers the ultra-stable atomic reference frequency stability to the target laser utilized for atomic sensors. The control transfer function of the closed-loop system is established to elucidate the process of perturbation suppression. It is illustrated that this method is robust against the disturbance to the laser and cavity by controlling the cavity with different parameters. After the long-term experimental test, the stability of the laser frequency locked on the fiber cavity achieves an Allan deviation of <semantics>9.9×10−11</semantics> and the detuning of the nearest atomic frequency resonance point is more than 200 GHz. Its stability and detuning value exceed previous reports.